Forecasting rubber production in Cotabato - Oxinio, Bernardo B. 1966- (2001)
This study aims to build a forecasting model for rubber production using regression analysis. The model can be used as an laternative to subjective estimation methods. The data used in the model-building were obtained from a Rubber Production Survey conducted by the researcher in the province of Cotabato, rubber- producing province. The reference period is 01 July to 31 December 1999.